المنهج النحوي عند علماء الهند في القرن التاسع عشر: دراسة تحليلية في كتاب «فوائد مكية» لعبد الحي اللكنوي - Dr. Musah Issa Zainudeen (Funun Arabiyyah: Journal of Arabic Education and Literature, 2026)
This study examines the grammatical approach adopted by nineteenth-century Indian scholars, focusing on Fawā’id Makkiyah by the prominent linguist ʿAbd al-Ḥayy al-Laknawī. It aims to analyze the theoretical foundations that underpin al-Laknawī’s treatment of Arabic grammatical issues, as well as to investigate his methods of explanation, use of examples, and interpretive strategies in engaging with classical grammatical doctrines. Particular attention is given to identifying the innovative aspects of his approach, especially in reconciling inherited grammatical principles with the intellectual demands of his time. The study further explores the extent to which the Indian scholarly and cultural milieu shaped al-Laknawī’s grammatical perspective, highlighting the interaction between local intellectual traditions and the broader corpus of Arabic linguistic scholarship. In addition, a brief comparative analysis is conducted to situate al-Laknawī’s methodology alongside those of his contemporaries, thereby clarifying both shared tendencies and distinctive features. Methodologically, this research employs a descriptive-analytical approach, combining textual analysis with contextual interpretation to provide a comprehensive understanding of the work under study. The findings reveal that al-Laknawī developed a nuanced and context-sensitive grammatical framework that both preserves classical foundations and introduces subtle interpretive refinements. This study contributes to the historiography of Arabic grammar by foregrounding the role of Indian scholars in its development and by demonstrating the significance of cross-cultural intellectual exchange